2020
DOI: 10.1101/2020.07.29.20164251
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of combination of interferon alpha-2b and interferon-gamma or interferon alpha-2b alone for elimination of SARS-CoV-2 viral RNA. Preliminary results of a randomized controlled clinical trial

Abstract: Objectives: IFN-alpha2b and IFN-gamma combination has demonstrated favorable pharmacodynamics for genes underlying antiviral activity which might be involved in the defense of the organism from a SARS-CoV-2 infection. Considering this we conducted a randomized controlled clinical trial for efficacy and safety evaluation of subcutaneous IFN-alpha2b and IFN-gamma administration in patients positive to SARS-CoV-2. Methods: We enrolled 19-82 years-old inpatients at the Military Central Hospital Luis Diaz Soto, Ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 54 publications
0
19
0
Order By: Relevance
“…The remaining trial comparisons included: favipiravir versus umifenovir [33]; umifenovir versus lopinavir-ritonavir [40]; umifenovir versus standard care [40]; novaferon versus novaferon plus lopinavir-ritonavir [45]; novaferon plus lopinavir-ritonavir versus lopinavir-ritonavir [45]; novaferon versus lopinavir-ritonavir [45]; alpha lipotic acid versus placebo [46]; baloxavir marboxil versus favipavir [41]; baloxavir marboxil versus standard care [41]; triple combination of interferon beta-1b plus lopinavir-ritonavir plus ribavirin versus lopinavir-ritonavir [38]; remdesivir for 5 days versus remdesivir for 10 days [37]; high-flow nasal oxygenation versus standard bag-valve oxygenation [44]; hydroxychloroquine versus chloroquine [48]; chloroquine versus standard care [48]; high dosage chloroquine diphosphate versus low dosage chloroquine diphosphate [50]; hydroxychloroquine plus azithromycin versus standard care [54]; triple combination of darunavir plus cobicistat plus interferon alpha-2b versus interferon alpha-2b [117]; lopinavir-ritonavir plus interferon alpha versus ribavirin plus interferon alpha [61]; ribavirin plus lopinavir-ritonavir plus interferon alpha versus ribavirin plus interferon alpha [61]; ribavirin plus lopinavir-ritonavir plus interferon alpha versus lopinavir-ritonavir plus interferon alpha [61]; lincomycin versus azithromycin [62];, 99-mTc-methyl diphosphonate (99mTc-MDP) injection versus standard care [63]; interferon alpha-2b plus interferon gamma versus interferon alpha-2b [64]; telmisartan versus standard care [66]; avifavir 1800/800 versus avifavir 1600/600 [67]; dexamethasone plus aprepitant versus dexamethasone [69]; anti-C5a antibody versus standard care [70]; azvudine versus standard care [73]; human plasma-derived C1 esterase/kallikrein inhibitor versus standard care [72]; icatibant acetate versus standard care [72]; icatibant acetate versus human plasma-derived C1 esterase/kallikrein inhibitor [72]; pulmonary rehabilitation program versus isolation at home [71]; auxora (calcium release-activated calcium channel inhibitors) versus standard care [74]; umbilical cord stem cell infusion versus standard care [75]; vitamin C versus placebo [76]; sofosbuvir plus daclatasvir versus standard care [80]; sofosbuvir plus daclatasvir plus ribavirin versus hydroxychloroquine plus lopinavir-ritonavir with or without ribavirin [79]; interferon beta-1b versus standard care [81]; calcifediol versus standard care [84]; recombinant human granulocyte colony–stimulating factor versus standard care [85]; intravenous and/or nebulized electrolyzed saline w...…”
Section: Resultsmentioning
confidence: 99%
“…The remaining trial comparisons included: favipiravir versus umifenovir [33]; umifenovir versus lopinavir-ritonavir [40]; umifenovir versus standard care [40]; novaferon versus novaferon plus lopinavir-ritonavir [45]; novaferon plus lopinavir-ritonavir versus lopinavir-ritonavir [45]; novaferon versus lopinavir-ritonavir [45]; alpha lipotic acid versus placebo [46]; baloxavir marboxil versus favipavir [41]; baloxavir marboxil versus standard care [41]; triple combination of interferon beta-1b plus lopinavir-ritonavir plus ribavirin versus lopinavir-ritonavir [38]; remdesivir for 5 days versus remdesivir for 10 days [37]; high-flow nasal oxygenation versus standard bag-valve oxygenation [44]; hydroxychloroquine versus chloroquine [48]; chloroquine versus standard care [48]; high dosage chloroquine diphosphate versus low dosage chloroquine diphosphate [50]; hydroxychloroquine plus azithromycin versus standard care [54]; triple combination of darunavir plus cobicistat plus interferon alpha-2b versus interferon alpha-2b [117]; lopinavir-ritonavir plus interferon alpha versus ribavirin plus interferon alpha [61]; ribavirin plus lopinavir-ritonavir plus interferon alpha versus ribavirin plus interferon alpha [61]; ribavirin plus lopinavir-ritonavir plus interferon alpha versus lopinavir-ritonavir plus interferon alpha [61]; lincomycin versus azithromycin [62];, 99-mTc-methyl diphosphonate (99mTc-MDP) injection versus standard care [63]; interferon alpha-2b plus interferon gamma versus interferon alpha-2b [64]; telmisartan versus standard care [66]; avifavir 1800/800 versus avifavir 1600/600 [67]; dexamethasone plus aprepitant versus dexamethasone [69]; anti-C5a antibody versus standard care [70]; azvudine versus standard care [73]; human plasma-derived C1 esterase/kallikrein inhibitor versus standard care [72]; icatibant acetate versus standard care [72]; icatibant acetate versus human plasma-derived C1 esterase/kallikrein inhibitor [72]; pulmonary rehabilitation program versus isolation at home [71]; auxora (calcium release-activated calcium channel inhibitors) versus standard care [74]; umbilical cord stem cell infusion versus standard care [75]; vitamin C versus placebo [76]; sofosbuvir plus daclatasvir versus standard care [80]; sofosbuvir plus daclatasvir plus ribavirin versus hydroxychloroquine plus lopinavir-ritonavir with or without ribavirin [79]; interferon beta-1b versus standard care [81]; calcifediol versus standard care [84]; recombinant human granulocyte colony–stimulating factor versus standard care [85]; intravenous and/or nebulized electrolyzed saline w...…”
Section: Resultsmentioning
confidence: 99%
“…A combination of IFNb1b, lopinavir–ritonavir, and ribavirin has been tested for treatment of hospitalized patients with COVID-19 in an open-label, randomized, phase 2 trial [16]. Similarly, IFNa2b and IFNg has also been evaluated in patients positive to SARS-CoV-2 [17]. Both treatments were shown to positively impact the resolution of the COVID-19 symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…In Cuba, a combination of interferon-α-2b and interferon γ on background therapy of LPV/r and chloroquine was successful in achieving viral clearance in 4 days in 78.6% of the patients compared to 40.6% of those receiving interferon-α-2b alone (53). A study of 81 hospitalized patients in Iran showed 28-day overall mortality significantly lower in an interferon β treated group than the control group (19% vs. 43.6% respectively, p = 0.015) (54).…”
Section: Resultsmentioning
confidence: 99%